Drug‐Drug Interaction Study to Assess the Effect of Cytochrome P450 Inhibition and Induction on the Pharmacokinetics of the Novel Cereblon Modulator Avadomide (CC‐122) in Healthy Adult Subjects. (6th June 2019) - Ogasawara, Ken; MacGorman, Kimberly; Liu, Liangang; Chen, Jian; Carayannopoulos, Leonidas N.; Zhou, Simon; Palmisano, Maria; Li, Yan
Abstract: Avadomide (CC‐122) is a novel immunomodulatory drug that binds to cereblon, a member of the Cullin 4‐RING E3 ubiquitin ligase complex. Avadomide has multiple pharmacologic activities including potent immune modulation, antiangiogenic, antitumor, and antiproliferative activity and is being evaluated as an oncology treatment for hematologic malignancies and advanced solid tumors. In vitro study has indicated that cytochrome P450 (CYP) 3A and CYP1A2 appear to be the major enzymes involved in the oxidative metabolism of avadomide. The effects of CYP3A inhibition/induction and CYP1A2 inhibition on the pharmacokinetics of avadomide in healthy adult subjects were assessed in 3 parts of an open‐label, nonrandomized, 2‐period, single‐sequence crossover study. Following a single oral dose of 3 mg, avadomide exposure when coadministered with the CYP1A2 inhibitor fluvoxamine was 154.81% and 107.59% of that when administered alone, for area under the plasma concentration‐time curve from time 0 to infinity (AUC0‐inf ) and maximum observed plasma concentration (Cmax ), respectively. Avadomide exposures, when coadministered with the CYP3A inhibitor itraconazole, were 100.0% and 93.64% of that when administered alone, for AUC0‐inf and Cmax, respectively. Avadomide exposures when coadministered with the CYP3A inducer rifampin were 62.83% and 88.17% of that when administered alone, for AUC0‐inf and Cmax, respectively. Avadomide was well tolerated when administered as a single oral dose of 3 mg alone or coadministered with fluvoxamine, itraconazole, or rifampin. These results should serve as the basis for avadomide dose recommendations when it is coadministered with strong CYP3A and CYP1A2 inhibitors and with rifampin.